PERAN PEMERINTAH DALAM PEMBERDAYAAN PETANI PADI DI DESA PARUMPANAI KECAMATAN WASUPONDA KABUPATEN LUWU TIMUR - Ahmar Ahmar; Mappamiring Mappamiring; Anwar Parawangi (Department of Public Administration, Muhammadiyah University of Makassar, 2016)
This study aims to determine the role of government in the empowerment of rice farmers and the determinant factor empowerment of rice farmers in the village Parumpanai Wasuponda Luwu Timur subdistrict. The study used a qualitative approach with descriptive analysis. This study uses a phenomenological type, data collection technique using the instrument in the form of interviews and observations. The results showed that the government's role in the empowerment of rice farmers in the village of Parumpanai already running although not yet fully effective, in addition to the farmers still feel the constraints of aid received assistance mainly seeds and fertilizers that are thought to increase agricultural production. This suggests that the absence of government's efforts to obtain quality seeds and fertilizers that are environmentally friendly affordable to the public in accordance with the conditions of agricultural land in the village of Parumpanai sehinggan to increase agricultural production community. Keywords: Role of Government, Farmer Empowerment Penelitian ini bertujuan untuk mengetahui peran pemerintah dalam pemberdayaan petani padi dan faktor determinan pemberdayaan petani padi di Desa Parumpanai Kecamatan Wasuponda Kabupaten Luwu Timur. Penelitian menggunakan pendekatan kualitatif dengan analisis deskriftif. Penelitian ini menggunakan tipe fenomenologis,Teknik pengumpulan data menggunakan instrumen berupa wawancara dan observasi. Hasil penelitian menunjukkan bahwa peran pemerintah dalam pemberdayaan petani padi di Desa Parumpanai sudah berjalan meskipun sepenuhnya belum efektif, disamping itu petani masih merasakan adanya kendala dari bantuan yang diterima terutama bantuan bibit dan pupuk yang dianggap bisa meningkatkan produksi lahan pertanian. Hal ini menunjukkan bahwa belum adanya upaya pemerintah mendapatkan bibit unggul dan pupuk yang ramah lingkungan yang terjangkau bagi masyarakat sesuai dengan kondisi lahan pertanian di Desa Parumpanai sehingga dapat meningkatkan produksi pertanian masyarakat. Kata Kunci : Peran Pemerintah, Pemberdayaan Petani